Formulasi Krim Tabir Surya Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) Terenkapsulasi Nanopartikel Kitosan: Uji Aktivitas Secara In Vitro - Irianti, Tatang (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Hylocereus polyrhizus peel contains many flavonoid compounds that have potential to become sunscreen. Nanoparticle technology in sunscreen preparations has the advantage of increasing activation, surface area, and better diffusivity in protecting the skin. The purpose of this study was to identify the physical properties and determine the effectiveness of sunscreen cream with Ki-Ekubuname nanoparticles as an active substance. The ionic gelation method is used in the manufacture of nanoparticles by optimizing the speed and duration of stirring. Then made formulations with varying levels of active substance. Formulations were prepared with varying levels of the active substance (FA without active substance, FB with 6% Ekubuname, F1, F2, and F3 with 2%, 4%, and 6% Ki-Ekubuname, respectively). The creams formed were observed for physical, chemical properties and sunscreen activity with in vitro. The results showed that Ekubuname has a total flavonoids of 2.034 ± 0.094 mg QE/g. All sunscreen formulas with Ki-Ekubuname nanoparticle active substances meet SNI 16-4399-1996 standard. Nano-size active substances have better performance, as evidenced by higher SPF values. Formula F3 has the best characterization with a homogeneous appearance, light brown color, soft texture, distinctive aroma, pH 5, viscosity 4,768.25 ± 210.80 cps, adhesiveness 6.15 ± 0.25 seconds, spreadability 6.01 ± 0.10 cm, O/W cream type, and SPF value 17.41 (ultra protection category).